Peran komunitas online muslim milenial dalam memoderasi pemahaman PAI diluar sekolah formal: Studi kasus di media sosial - Dwi Marpendra, Zikri; Sopiamdi Harahap, Mulia; Neni (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to analyze the role of millennial Muslim online communities in moderating the understanding of Islamic Religious Education (PAI) outside formal institutions, particularly through social media platforms. The research employs a qualitative approach with a case study design, involving data collection through in-depth interviews, participatory observation, and digital content analysis. The data were analyzed thematically to identify strategies, impacts, challenges, and opportunities of online communities in promoting religious moderation. The findings indicate that online communities play a significant role in developing critical, inclusive, and interactive religious literacy, utilizing digital media to foster dialogue among members. The strategies implemented, such as online studies, educational content, and interactive discussions, effectively enhance millennial understanding of PAI. However, these communities also face challenges including misinformation, digital religious performance pressure, and limited resources. The study concludes that millennial Muslim online communities have the potential to become key agents of religious moderation relevant to contemporary needs and can serve as strategic partners for Islamic educational institutions in advancing PAI in the digital era.